Optimizing the Quality of Public Services in Village Government: A Qualitative Study in Kertawinangun Village, Mandirancan District, Kuningan Regency - Rexy Nakula Urbaningrum; Merlinda Intan Fauziah (Journal Research of Social Science, Economics, and Management, 2026)
Public services at the village government level are strategic instruments in realizing accountable governance and supporting the economic development of rural communities. This research aims to analyze the quality of public services and formulate a service optimization strategy in Kertanginangun Village, Mandirancan District, Kuningan Regency. The research uses a qualitative approach with an intrinsic case study design. Data collection was carried out through in-depth interviews, participatory observations, and documentation studies during the January-March 2024 period. The informants consist of village heads, village officials, BPD members, and service user communities. Data analysis used the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and conclusion drawing by triangulating sources and methods. The results of the study show that the quality of service is relatively strong in the dimensions of empathy and social capital that build public trust. However, in the dimensions of reliability and responsiveness, there is still a dependence on certain apparatus, the standardization of procedures has not been optimal, and the digitization of administration is incremental. The findings show that social capital plays a role as a moderation variable in service implementation. Service optimization requires strengthening institutional capacity, standardizing SOPs, gradual digitalization, and institutionalizing community participation mechanisms. This study develops a social-administrative interaction model as a conceptual framework for village services that are adaptive to the local social context.